Mastering the body. (3rd December 2018) - Kern, Friederike
Abstract : Recent interactional studies of multimodal interaction have shown how touch can be used as a form of social control in adults' directives to children, or as a way of guiding children into embodied politeness. Using multimodal interactional analysis grounded in conversation analysis, this paper aims at exploring how touch is used as a semiotic resource to socialize young children between 4 and 5 years of age into appropriate ways of presenting the body in public. The focus will be on moments when the child's body becomes the subject of correction while some other action is going on. In those moments, touch is used as manual guidance to change and correct children's body position or bodily conduct. These corrections shed light on what are considered appropriate forms of bodily conduct in public, and how children are manually guided towards established norms of such conduct. The study aims at adding to our understanding on how 'haptic sociality' (Goodwin 2017) contributes to socializing children into appropriate bodily conduct in interaction.